2006
DOI: 10.1189/jlb.1105668
|View full text |Cite
|
Sign up to set email alerts
|

Release of surface-expressed lactoferrin from polymorphonuclear neutrophils after contact with CD4+T cells and its modulation on Th1/Th2 cytokine production

Abstract: It is conceivable that a membrane component(s) is transferred from antigen-presenting cells to T cells after antigenic stimulation. However, it is not clear whether a certain membrane component(s) is transferred from polymorphonuclear neturophils (PMN) to T cells for immunomodulation. In the presence study, we cocultured two of the three autologous cells-PMN, CD4+ T, and red blood cells (RBC)-homotypically or heterotypically for 1 h. Spontaneous membrane exchange between autologous PMN-PMN and PMN-CD4+ T but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Furthermore, hLF shares only 68% sequence with its bovine counterpart (21, 34 -36). Therefore, our results may have more relevance for understanding the effect(s) of lactoferrin on human immune cells and immunity than those studies in which the bovine lactoferrin was used (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, hLF shares only 68% sequence with its bovine counterpart (21, 34 -36). Therefore, our results may have more relevance for understanding the effect(s) of lactoferrin on human immune cells and immunity than those studies in which the bovine lactoferrin was used (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 90%
“…Neutrophils are a major source of lactoferrin. Normal lactoferrin levels in the blood are very low with 1 μg/mL, but under septic conditions these can rise up to 200 μg/mL and are likely to be higher at the inflammatory site itself (160). Besides its antimicrobial activity, lactoferrin exhibits immune-modulating activities.…”
Section: Neutrophil-derived Cationic Polypeptidesmentioning
confidence: 99%
“…LF stimulates the differentiation of T cells from immature precursors (Li et al 2006). Studies performed under nonpathogenic conditions have indicated that LF supports the proliferation and differentiation of Th cells into Th1 or Th2 cell types.…”
Section: Introductionmentioning
confidence: 99%